2009
DOI: 10.1007/s11664-009-0708-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Well-Tiled γ-Na x Co2O4 by a Novel and Simple Sodium Alginate Gel Method and Its Electrical Properties

Abstract: In this paper, a novel and simple sodium alginate (SA) gel method was developed to prepare c-Na x Co 2 O 4 . This method involved the chemical gelling of SA in the presence of Co 2+ ions by cross-linking. After calcining at 700°C to 800°C, single-phase c-Na x Co 2 O 4 crystals were obtained. The arrangement of about 1 lm to 4 lm flaky particles exhibited a well-tiled structure along the plane direction of the flaky particles. SA not only acted as the control agent for crystal growth, but also provided a Na sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…3b). Similar behavior was observed by Zhang et al 27 for alginate gel based synthesis of tiled Na x Co 2 O 4 crystals. The entrapment and crosslinking by PAA is crucial for forming the autocombusted flakes: if citric acid is used in place of PAA and the ratio of carboxylic moieties to the number of metal cations is fixed (2 : 1), flake-like formations do not occur after autocombustion and the volume of the autocombusted form is much smaller compared to the case with PAA (i.e., less than 1/3).…”
Section: Resultssupporting
confidence: 87%
“…3b). Similar behavior was observed by Zhang et al 27 for alginate gel based synthesis of tiled Na x Co 2 O 4 crystals. The entrapment and crosslinking by PAA is crucial for forming the autocombusted flakes: if citric acid is used in place of PAA and the ratio of carboxylic moieties to the number of metal cations is fixed (2 : 1), flake-like formations do not occur after autocombustion and the volume of the autocombusted form is much smaller compared to the case with PAA (i.e., less than 1/3).…”
Section: Resultssupporting
confidence: 87%
“…[2][3][4][5] Research results have shown that the thermoelectric properties of polycrystalline sintered bulk NaCo 2 O 4 can be improved by obtaining more highly oriented crystals. 2,3 Furthermore, properties of NaCo 2 O 4 powders such as the particle size and the morphology, which are determined by the preparation technology applied, [6][7][8][9] are related to the thermoelectric properties of polycrystalline sintered bulk Na x Co 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%